Fatal intoxication of an infant caused by antiepileptic drugs - case report - Pančić, Dimitrije; Vujović, Maja; Kostić, Emilija; Antović, Aleksandra; Pinterović, Bogdan; Miljković, Milica; Stojanović, Ivan (Archives of Pharmacy, 2022)
Antiepileptic drug poisoning in children can manifest in multiorgan dysfunctions of varying degrees, ranging from discretely expressed symptoms to severe and life-threatening complications. This paper presents the fatal case of a male infant aged three and a half months, whose autopsy was performed on suspicion of medical drug poisoning. After three months of hospitalization due to intrapartum asphyxia, the infant was discharged for home treatment under the diagnosis "Epilepsy idiopathica (focalis) (partialis) et syndromata epileptica cum impetu simplici partiali." Therapy with Levetiracetam, Valproic acid, and Phenobarbitone was prescribed. Three days after the discharge from the hospital, the infant was hospitalized again due to drowsiness and dyspnea, which deepened within 24 hours to coma, respiratory arrest, and death. During the hospital treatment, a toxicologic-chemical analysis of blood showed Levetiracetam’s presence in the concentration of 23.67 mg/L and Phenobarbitone at 78 mg/L. An autopsy determined a non-specific finding on the internal organs, with severe edema of the brain and lungs. Toxicological-chemical analysis of cadaveric tissue samples revealed the presence of Levetiracetam at a concentration of 21.95 mg/L and Phenobarbitone at a concentration of 65 mg/L. It was concluded that the death was violent and occurred due to antiepileptic drug poisoning. Investigative actions in the criminal procedure established that the mother ordinated advised therapy to the child in doses ten times higher than the prescribed ones. At the same time, whether the poisoning occurred negligently or intentionally remained unknown.